Exploring dog saliva as a non-invasive alternative to blood sampling for chemical exposome studies: analysis of synthetic phenolic antioxidants and PFAS - Weiss, Jana M.; Engelhardt, Josefin; Franco Martínez, Lorena; Tvarijonaviciute, Asta (Frontiers in Veterinary Science, 2026)
BackgroundHumans and companion animals are continually exposed to mixtures of synthetic chemicals from household products, textiles, food, and personal care items. Epidemiological studies of emerging contaminants typically rely on invasive blood sampling, whereas saliva presents a non-invasive and cost-effective alternative matrix that reflects both local and systemic physiological changes. In this pilot study, paired dog saliva and blood serum were analysed for two chemical groups of concern, that is, synthetic phenolic antioxidants (SPAs) and per- and polyfluoroalkyl substances (PFAS), to investigate whether saliva can be used for chemical exposome studies.MethodsBlood serum and saliva samples of a total of 30 dogs were included in this study. All dogs were privately owned, representing different breeds, and were presented to private veterinary clinics in the Murcia Region, Spain. Samples were analysed using acetonitrile for denaturation and extraction, and clean-up using enhanced matrix removal powder. The extracts were analysed using complementary liquid and gas chromatography coupled with mass spectrometers. Dogs were divided into three groups (n = 10 per group): healthy normal-weight dogs, healthy obese dogs, and dogs diagnosed with mammary tumours.ResultsFourteen SPAs (including five metabolites) and eight PFAS were quantified in the dog’s saliva and/or serum. Generally, the levels were higher in serum than in saliva. None of the dogs were free of contaminants. The SPA levels were dominated by the 2,4-di-tert-butylphenol (2,4-DBP), found in 93% of saliva and 100% of serum samples, ranging from <LOQ-860 ng/g in saliva and 130–2,100 ng/g in serum. The levels of PFAS were dominated by perfluorononanoic acid (PFNA) and perfluorosulfonic acid (PFOS), which were quantified in more than 70% of the samples. No correlation between levels and the three groups, or the paired serum and saliva samples could be established.ConclusionThis study confirmed that SPAs and PFAS can be found in the saliva of dogs. The levels of PFAS in dog’s serum were similar to those generally reported in human blood. Furthermore, this study confirms that dogs are exposed to SPAs at concerningly high levels, given the limited knowledge regarding their toxicity.